A novel homozygous frame‐shift variant in the LHCGR gene is associated with primary ovarian insufficiency in a Pakistani family. Issue 3 (17th July 2018) - Zielen, A.C.; Khan, M.J.; Pollock, N.; Jiang, H.; Ahmed, J.; Nazli, R.; Jabeen, M.; Yatsenko, A.; Rajkovic, A.
Abstract :